Diabetes Medication Assistance Service Stage 1: impact and sustainability of glycaemic and lipids control in patients with Type 2 diabetes - Krass, I.; Mitchell, B.; Song, Y.; Stewart, K.; Peterson, G; Hughes, Jeffery; Smith, L.; White, L.; Armour, C (Diabetes UK, 2011)
Aims: To investigate (i) optimal intensity (four visits vs. six visits) and duration (6 vs. 12 months) of the Diabetes Medication Assistance Service in community pharmacy and (ii) sustainability of improvements in patients’ diabetes control associated with differing intensities of intervention. Methods: A national quota sample of 90 community pharmacies in Australia were randomly assigned into group 1 (6-month Diabetes Medication Assistance Service) or group 2 (12-month Diabetes Medication Assistance Service) and subsequently recruited a total of 524 patients. A wide range of clinical (HbA1c, blood pressure, lipids) and quality-of-life outcome measures were assessed.Results: The 6- and 12-month Diabetes Medication Assistance Service resulted in significant and similar reductions in HbA1c (−0.9 mmol/mol; 95% CI −0.7 to −1.1) –, total cholesterol (−0.3 mmol/l; 95% CI −0.1 to −0.4) and triglycerides (−0.3 mmol/l; 95% CI −0.1 to −0.5). There was also a significant reduction in the number of patients who were at risk of having a cardiovascular event in the next 10 years. For the subset of patients for whom data were available at baseline, completion and 18 months, improvements in HbA1c and total cholesterol were sustained at 18 months and triglycerides showed a further improvement at 18 months. Conclusions: The Diabetes Medication Assistance Service resulted in significant improvements in diabetes control that were independent of intensity and duration of the service and showed evidence of being sustained at 18 months. The extent and sustainability of clinical improvements achieved by the Diabetes Medication Assistance Service, together with the resulting reduction in cardiovascular risk, should translate into future cost savings to healthcare systems by delaying and reducing diabetes-related complications.